a ! ⋅ b ! = a ! + b ! + c !
How many ordered triplets of positive integers ( a , b , c ) exists for which the above equation is satisfied?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great explanation!
S i n c e a a n d b a r e i n t e r c h a n g e a b l e , w e c a n s a f e l y a s s u m e a = b o r a > b . N o t e t h a t n ! > 0 , a n d s o m i n i m u m c ! = 1 . I f b = 1 , a ! ∗ b ! < a ! + b ! , ⟹ a = b > 1 I f a = b = 2 , a ! ∗ b ! = a ! + b ! + 0 , b u t c ! = 0 , ∴ a = b = 2 n o t a s o l u t i o n . 1 2 = 3 ! ∗ 2 ! = 3 ! + 2 ! + 4 . B u t c ! = 4 . n o s o l u t i o n . N e x t 3 ! ∗ 3 ! = 3 6 = 3 ! + 3 ! + 2 4 s o c ! = 2 4 a n d c = 4 . S o l u t i o n ( a , b , c ) = ( 3 , 3 , 4 ) o n l y . S i n c e a > 3 , a ! ∗ b ! = a ! + b ! + X . B u t X i s n e v e r = c ! .
I missed it for I took (3,3,4),(3,4,3),(4,3,3) as solutions !!!
i don't know no. theory i just checked with some no.s and guessed it
Sorry there was a slight mistake in my original solution, but it has been fixed now.
Problem Loading...
Note Loading...
Set Loading...
Firstly, lets assume without loss of generality that a ≤ b . Testing a = 1 and a = 2 leads to no solutions, so a ≥ 3 . Now dividing the whole equation by a!: b ! = 1 + a ! b ! + a ! c ! ( 1 ) From this we can see that c ≥ a otherwise the RHS is not an integer, but the LHS is, which forms a contradiction. Looking at b and c we have 2 possibilities: c < b o r c ≥ b . The first possibility implies that a ! b ! = a ! + b ! + c ! < 3 b ! ⇒ a ! < 3 . This is a contradiction so c ≥ b . However b = c leads to the following equation: 1 = a ! b ! ( a ! − 2 ) > 1 so c > b . Now looking at (1): b ! a n d a ! c ! are both even so a ! b ! is odd. Testing b=a+1 in the original equation gives: a ! ( a + 1 ) ! = a ! + ( a + 1 ) ! + c ! ⇒ ( a + 1 ) ! = a + 2 + a ! c ! = ( a + 1 ) + 1 + ( a ! c ! ) so (a+1) divides every term except 1 which is not possible. This contradiction means that a =b. (i.e. 3 ≤ a = b < c ). From (1) we obtain: a ! − 2 = a ! c ! of which 3 doesn't divide either side. This implies that RHS = a+1 or (a+1)(a+2). The first produces a ! − a = 3 ⇒ a ∣ 3 and the 2nd produces a ! − a ( a + 3 ) = 4 ⇒ a ∣ 4 . Hence, a = 3 or 4, but testing leads to only a = 3. ∴ ( a , b , c ) = ( 3 , 3 , 4 ) i s a u n i q u e s o l u t i o n